Managers and basic education teachers: the implications of its role with the effectiveness of Technical School Boards - Manuel Ortega Muñoz; Zaret Jazmín Hernández Soto (ADIDE Federación, 2015)
This letter is part of a broader investigation that deals with the functioning of the School Technical Councils in the elementary schools in the state of Durango, Mexico. In this part, they were raised the following objectives: a) Identify what level of implications of the role of principals and teachers in the effective functioning of the School Technical Councils, b) Identify the implications of the role of principals and teachers are regarding compliance with the objectives of the School Technical Councils in schools of basic education in the state of Durango and c) Identify the implications of the role of principals and teachers regarding the exercise of the powers of the Technical School Councils in schools are Basic education in the state of Durango, Mexico. To achieve the objectives was carried out an exploratory, descriptive, correlational, cross-sectional non-experimental study. Information gathering was conducted by survey method using a questionnaire applied to 1243 principals, group teachers, support teachers and of basic education in the State of Durango, México. Its main results support the conclusion that the gender implications regarding the effective functioning of the School Technical Councils in the elementary schools in the state of Durango have a low level, analyzing its dimensions: achievement of objectives and exercise of powers.